Perancangan Sistem Pemantauan untuk Meningkatkan Pencapaian Realisasi dengan Perencanaan Painting di PT X - Vanessa Angela Chionardes; I Gede Agus Widyadana (Jurnal Titra, 2022)
PT X as a company that produces various types of bicycles has problems which one of them is painting process that does not produce output on time and in the right amount according to PPIC’s schedule. Based on Fishbone Diagram and Pareto Chart analysis, the most affecting factors are method, material, and environment.  The method factor is repair work has not been monitored well so there might be work delay. The monitoring system design in this research begins with improving the flow, then continued with the making of SOP and database in Google Sheets. The average percentage of realization accomplishment with planning from February until March (before implementation) is 32.09% and it increases to 50.01% from April until May (after implementation). Monitoring system can also show painting repair team performance that is presented by the percentage of daily repair accomplishment that has an average of 72.13% in April and 52.62% in May which is still below the target.